Portal placement in elbow arthroscopy and risk of injury to major nerves and vessels: a cadaveric study - Joseph, Mathew; Goyal, Tarun; Goel, Prabhat; Sharma, Urvi; Devi, Bharti; Singla, Mukesh; Singh, Brijendra (International Journal of Research in Orthopaedics, 2025)
Background: Elbow arthroscopy is one of the popularly used surgical procedures in treating various elbow pathologies. Cadaveric data on the safety of arthroscopic portals and data on outcome following an arthroscopic procedure of elbow is lacking. This study aimed to measure the distance of 5 arthroscopic portals from 7 selected neurovascular structures in cadaveric elbow in 3 different elbow positions. Methods: Observational study was conducted at the All India Institute of Medical Science (AIIMS) Rishikesh, Uttarakhand India. A total 20 soft embalmed cadaveric elbow were dissected following placement of arthroscopic portals at different elbow positions. Data were compared and analysed using SPSS software with ANOVA test. Results: Medial cutaneous nerve of forearm (MCNF) was injured (5/1020) which is <0.5% when using superomedial (SM) and anteromedial (AM) portals. Statistically significant change was found while considering Lateral cutaneous nerve of forearm (LCNF) from anterolateral (AL) portal at various angles of the elbow and brachial artery (BA) from AM portal. Rest of all structures did not show any statistical significance on changing angles of elbow flexion. Conclusions: Minor nerves are at risk in certain portals. Position of AL portal is safer when compared to AM portal. With proper surgical guidelines, elbow arthroscopy is safe and much useful procedure which help the operating surgeon to choose the appropriate portal and also may aid in minimizing trauma to underlying structures during intervention.